2017
DOI: 10.1371/journal.pone.0173431
|View full text |Cite
|
Sign up to set email alerts
|

Highs and lows, ups and downs: Meteorology and mood in bipolar disorder

Abstract: Seasonal variation of manic and depressive symptoms is a controversial topic in bipolar disorder research. Several studies report seasonal patterns of hospital admissions for depression and mania and variation in symptoms that appear to follow a seasonal pattern, whereas others fail to report such patterns. Differences in research methodologies, data analysis strategies, and temporal resolution of data may partly explain the variation in findings between studies. The current study adds a novel perspective to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Recently, another important study, conducted on eleven BD type I patients by Bullock and colleagues, stressed the importance of maximum temperature to predict the transition from depressed to manic mood on consecutive days, particularly in the absence of a direct sunshine hours effect on mood. The authors showed that, in a small sample of bipolar patients, daily maximum temperature predicted a clinically relevant mood change, in particular a transition into manic mood states [23]. Despite the fact that almost all cerebral processes are sensitive to temperature fluctuations, which were reported to intrinsically modulate behavioral changes and reflexively generate autonomic responses [49], the authors suggested an active involvement of maximum temperature in a model in which its effect was likely mediated by sleep disruption [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, another important study, conducted on eleven BD type I patients by Bullock and colleagues, stressed the importance of maximum temperature to predict the transition from depressed to manic mood on consecutive days, particularly in the absence of a direct sunshine hours effect on mood. The authors showed that, in a small sample of bipolar patients, daily maximum temperature predicted a clinically relevant mood change, in particular a transition into manic mood states [23]. Despite the fact that almost all cerebral processes are sensitive to temperature fluctuations, which were reported to intrinsically modulate behavioral changes and reflexively generate autonomic responses [49], the authors suggested an active involvement of maximum temperature in a model in which its effect was likely mediated by sleep disruption [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors investigated the role of these factors in bipolar patients with significant impact on both the onset and course of BD and consequently on sleep-wake cycle, mood and energy [10,12,13,14,15,16]. Furthermore, certain authors indicated that environmental factors, such as humidity, day length, ultraviolet radiation, temperature, rainfall/atmospheric pressure or airborne allergens exert a significant role on the admission of BD patients, particularly in (hypo)manic phase, or when they exhibit specific symptoms such as psychosis, impulsiveness, and suicidal behavior/aggression [14,17,18,19,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…6 In another study, daily maximum temperature was the only meteorological variable to predict clinically relevant mood change; this suggests that increases in temperature are associated with higher odds of a transition into manic mood states. 7 However, there are no significant results showing that environmental factors such as exposure to daylight are associated with seasonal patterns. 8 It has also been reported that patients with bipolar depression can heal more quickly in rooms receiving more sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…Psychogenic non-epileptic seizures (PNES) are linked to psychiatric comorbidities including post-traumatic stress, anxiety and depressive disorders 38 , which may show similar modulating factors as multi-day epileptic rhythms. By the same token, other episodic psychiatric conditions may adhere to slow modulation, including bipolar disorder 39,40 , depression 41,42 and other psychopathologies 43 . Studying multi-day cycles within non-epileptic populations is likely to prove crucial to fully understand the mechanisms of epileptic rhythms.…”
Section: Discussionmentioning
confidence: 99%